Acquired Clitoromegaly Cyst: Consequence of Persistent Unorthodox Practice in the 21st Century (2019)
Objective: To present case report a patient with clitoral cyst, following type II female genital cutting performed in childhood, management and literature review. Design: Report of cases managed and review of available current literatures. Setting: University College Hospital Ibadan. Patients: The case was a 30 year old Para 2+0 , 2 alive, known hypertensive, with perineal swelling since childhood. She presented 30 years later with increasing size of the clitoral swelling associated with pain. Management: Surgical excision of the cyst following thorough evaluation of the patients. Results: Better cosmetic outcome, vulvar discomfort subsided and improved sexual satisfaction post-operatively. Conclusion: While a good cosmetic and stoppage of vulvar discomfort can be managed with acceptable outcomes, these case, again, brings to attention of persistence of unacceptable female genital cutting with attendant effects even in the 21st century. Also, to let us know that there is need for more and continuous awareness creation of the need to stop this dehumanizing practice, of female genital cutting, which is of no health importance, rather numerous adverse sequelae.